Turf Toe in a Taekwandoo Player: Case Report - Sahin, Namik (Asist Group, 2004)
Metatarsophalengeal joint injuries of great toe termed as ‘’turf toe” can occur in many sportive activities. However, it has not been reported before in taekwondoo players. These injuries may result in significant morbidity. Turf toe injuries, which are mainly treated with conservative methods, occasionally require surgery. In this case report, we present a surgically treated turf toe in a taekwondoo player.